Complex Permeability and Transport Properties of Zn Substituted Cu Ferrites (Journal of Bangladesh Academy of Sciences, 2010)
Zn doped Cu ferrite of the composition Cu1-xZnxFe2O4 ferrites for x = 0, 0.1, 0.2, 0.3, 0.4, 0.5,0.6 prepared by standard double sintering ceramic technique. SEM micrograph of all the samplesrevealed that the grain sizes decrease gradually with the increase of Zn content and has greatinfluence on the magnetic and transport properties. Permeability is found to increase with increasein Zn content up to x = 0.4 and then slightly decreases with further increase in Zn. The values ofrelative quality factor (RFQ) changes with Zn concentration. Room temperature DC resistivitychanges significantly with Zn addition. The variation of the resistivity versus frequency was studiedand the dielectric constant of the system has a variation quite opposite to that of the AC resistivity.Dielectric constant shows the normal behaviour of the ferrite materials that can be explained by theinterfacial polarization as predicted by Maxwell and Wagner.Key words: Microstructure; Initial permeability; Dielectric constant; DC resistivityDOI: 10.3329/jbas.v34i1.5486Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 1-8, 2010